2013
DOI: 10.1186/2045-8118-10-34
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint changes in CSF composition associated with different aetiologies in human neonatal hydrocephalus: glial proteins associated with cell damage and loss

Abstract: BackgroundIn hydrocephalus an imbalance between production and absorption of cerebrospinal fluid (CSF) results in fluid accumulation, compression and stretching of the brain parenchyma. In addition, changes in CSF composition have a profound influence on the development and function of the brain and together, these can result in severe life-long neurological deficits. Brain damage or degenerative conditions can result in release of proteins expressed predominantly in neurons, astroglia, or oligodendroglia into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…Interpretation of this data will need to be considered if the CSF was of ventricular or lumbar origin, as there is evidence of a rostrocaudal gradient with higher CSF GFAP levels in ventricular CSF (Tarnaris et al, 2010). Likewise, the presence of blood in the CSF was related to higher CSF GFAP levels in hydrocephalus (Naureen et al, 2013). This may partly explain the considerable elevation of ventricular CSF GFAP levels following SAH which required extra ventricular drainage for management of secondary hydrocephalus (Petzold et al, 2006).…”
Section: Hydrocephalusmentioning
confidence: 94%
“…Interpretation of this data will need to be considered if the CSF was of ventricular or lumbar origin, as there is evidence of a rostrocaudal gradient with higher CSF GFAP levels in ventricular CSF (Tarnaris et al, 2010). Likewise, the presence of blood in the CSF was related to higher CSF GFAP levels in hydrocephalus (Naureen et al, 2013). This may partly explain the considerable elevation of ventricular CSF GFAP levels following SAH which required extra ventricular drainage for management of secondary hydrocephalus (Petzold et al, 2006).…”
Section: Hydrocephalusmentioning
confidence: 94%
“…Myelin basic protein (MBP), a protein generally associated with the formation of myelin in oligodendrocytes, is elevated in the CSF of hydrocephalic patients (Beems et al, 2003; Longatti et al, 1993; Longatti et al, 1994; Naureen et al, 2013). Additionally, defects in myelination have been shown to result from hydrocephalus (Di Curzio et al, 2013; Goto et al, 2008; Hanlo et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The pathophysiology of hydrocephalus is multifactorial with a pervasive impact on the brain. Previous studies of CSF composition in hydrocephalus (reviewed in [ 10 16 ] have suggested that periventricular axonal damage and demyelination [ 13 , 17 , 18 ], apoptosis [ 19 ], disruption of the blood-brain barrier [ 20 ], reduced cerebral blood flow accompanied by hypoxia and ischemia [ 14 ], altered metabolism [ 21 ], reductions in neurotransmitters and neuromodulators [ 18 , 22 24 ], and neuroinflammation [ 13 , 25 31 ] may all play important roles in the progression of hydrocephalus. Older studies of various biomarkers associated with these mechanisms in developing brains have suggested that none were robust enough to predict clinical outcome [ 10 , 32 ], but more recent reports, especially those on adult and aging patients with idiopathic normal pressure hydrocephalus (iNPH), indicate that CSF levels of Aβ 42 and tau, correlate well with clinical signs and symptoms [ 11 , 12 , 15 , 18 , 32 39 ].…”
Section: Discussionmentioning
confidence: 99%